Is the UNDP Declared Human Development for Everyone Possible in Real Life? - Komarova, Vera; Vasserman, Yuriy; Selivanova-Fyodorova, Natalya (European Scientific Journal, ESJ, 2018)
The law of normal distribution applied to human development states that an equal level of development of countries (regions, and people) at one point in time cannot be achieved, and under any level of average development there will always be those lagging behind this level and those ahead of it. The main research issue within the framework of this article is the following: what happens beyond the average indicators of human development in real life, and is it possible to achieve the equally high level of human development for everyone? The authors answer this question with the help of diachronic and synchronic analysis of the Human Development Index (HDI) in the period 1990 – 2017 with respect to compliance of the HDI variance to normal distribution. Using cluster analysis, the authors obtained the results testifying that the modern world is increasingly divided into groups of countries (“worlds”) every one of which has its own average level of human development, and the HDI of the countries within each group varies in accordance with the Gauss curve. These four “worlds“ generally coincide with the UNDP division of countries into four groups - very high human development, high human development, medium human development, low human development. The authors came to the conclusion that the human development as the dynamic process is possible. But it is impossible to achieve the same level of human development for everyone without differences in the development levels between several groups of countries (several “worlds”) and within one group of countries (one “world”).